The structure and flow of disordered wet foams - O'Donovan, Cathal B. (Trinity College (Dublin, Ireland). School of Physics, 2014)
This thesis concerns the structure and flow properties of wet foams. We primarily use computer simulations of soft particles to model the behaviour of disordered wet foams. We investigate the properties of 2D and 3D polydis- perse packings of soft particles and the flow of 2D soft discs as model systems for wet foams.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin